Time-varying linkages between tourism receipts and economic growth in South Africa - Balcilar, Mehmet; van Eyden, Renee; Inglesi-Lotz, Roula; Gupta, Rangan (Routledge Journals, Taylor & Francis Ltd, 2014)
The causal link between tourism receipts and GDP has recently become a major focus in the tourism economics literature. Results obtained in recent studies about the causal link appear to be sensitive with respect to the countries analysed, sample period and methodology employed. Considering the sensitivity of the causal link, we use rolling window and time-varying coefficient estimation methods to analyse the parameter stability and Granger causality based on a vector error correction model (VECM). When applied to South Africa for the period 1960-2011, the findings are as follows: results from the full-sample VECM indicate that there is no Granger causality between tourism receipts and GDP, while the findings from the time-varying coefficients model based on the state-space representation show that tourism receipts have positive-predictive content for GDP for the entire period, with the exception of the period between 1985 and 1990. Full-sample time-varying causality tests show bidirectional strong causality between tourism receipts and GDP.
Keywords: tourism receipts; economic growth; time-varying causality; time-varying parameter model; C32; L83; O40